Symbolism of Movement in Widya Prakrti Dance: A Phenomenological Analysis of Cultural and Spiritual Interpretation - I Wayan Gede Lamopia; Riza Wulandari; Putu Setyarini (Gondang: Jurnal Seni dan Budaya, 2025)
Artistic and cultural degradation has recently emerged amidst the rapid spread of digitised information. This research aims to anticipate the degradation of the understanding of the art of cultural identity by finding historical records, symbols and meanings in the Widya Prakrti Dance owned by the maestro of the island of Bali. It is essential to conduct an in-depth study that has an impact on the millennial generation in the digital era not to leave the tradition of meaning symbols in their cultural identity. The method used in this research is qualitative phenomenology. Data collection techniques in the form of in-depth interviews, documentation and literature studies and studied using George Herbert Mead's theory of symbolic interactionism. The participants are divided into 2 groups, namely key informants of 2 people and companion informants of 13 people who will complete the data presentation. The findings of this study examine the history, meaning and symbols of the Widya Prakrti dance. The sacredness of this dance is a manifestation of love for God and Lord Vishnu as the strength and balance of life.